HUKUM ADAT SEBAGAI PRANATA HUKUM PENANGKAL ARUS GLOBALISASI - Ana Suheri (Fakultas Hukum Universitas PGRI Palangkaraya, 2017)
Abstract : Globalization is an age in which the increasingly border territorial, economic, political, cultural and other boundaries between a national entity in the international world. Globalization is usually followed by a modernization, modernization as a social movement is actually revolutionary, from which tradition originally became modern. In addition, modernization also has a complex, systematic nature, a global movement that will affect all human beings, through a gradual process toward hemogenisation and progressive nature. The negative impacts of globalization, and of course also modernization, will be even more obvious if we do more specific observations of the village community. However, as the economy began to improve, supported by the increase of infrastructure, the existing cultural values began to fade and adherence to the customary law began to fade, but this has not been accompanied by awareness and dherence to the high state law. It certainly becomes a negativistic transition, where the peculiarities of indigenous peoples begin to be eroded by globalization and modernity. Keywords : The Characteristics of Indigenous Law In the Flow of Globalization